The impact of the RoboticScope™ exoscope on cleft lip and palate surgery: surgical advances stimulated by last generation technologies - Sanchez-Castrejon, Esperanza; Llamas-Ostos, Alejandra N.; Fukumoto-Inukai, Kenzo A.; Cabrera-Cifuentes, Maria M.; Guevara-Valmaña, Osvaldo I.; Caballero, Ricardo R.; Wagner, Rogelio M. (International Surgery Journal, 2026)
RoboticScope™ (RS™) is a robotic exoscope that integrates three-dimensional high-definition visualization with hands-free control, offering potential advantages in microsurgical procedures. Cleft lip and palate (CLP) repair require a small and deep surgical field, precise tissue handling, and presents ergonomic challenges for surgeons and limitations in surgical teaching. This case series describes. The feasibility, safety, advantages, and limitations of using RS™ during cheiloplasty and palatoplasty. Eight patients with unilateral cleft lip and/or palate were included: four cheiloplasties and four palatoplasties, half performed with RS™ and half with conventional techniques by the same surgical team. Intraoperative variables, postoperative outcomes, and surgeon satisfaction were evaluated. No differences were observed between groups regarding bleeding, aesthetic-functional outcomes, or short-term complications at six months. Surgical time was longer when using RS™, reflecting the initial learning curve. Surgeons reported superior visualization, improved ergonomics, and enhanced educational value with RS™, allowing real-time sharing and recording of procedures. Despite limitations related to equipment cost and unfavorable angles in specific surgical steps, RS™ demonstrated technical feasibility and safety in CLP surgery. This case series represents the first clinical report of RS™ use in cleft lip and palate repair and suggests that it is a promising adjunct to conventional techniques, particularly for microsurgical precision, ergonomics, and surgical education.